Перспективи пошуків вуглеводнів у девонських відкладах Волино-Поділля за результатами зонального прогнозу - Гоник, І.; Гаврилко, Г.; Гоник, О. (Геологія і геохімія горючих копалин, 2010)
Повторно виконано зональний прогноз нафтогазоносності девонських відкладів Волино-Подільської нафтогазоносної області. Нові фактичні матеріали буріння і
геофізичних досліджень дозволили детальніше розчленувати розріз та вивчити тектоніку девонського комплексу. Найважливіші критерії нафтогазоносності нанесено
на результативну карту Волино-Подільської нафтогазоносної області. Виділено території з різною перспективністю. Рекомендовано напрями подальших геологорозвідувальних робіт: пошуково-розвідувального та оціночно-параметричного буріння, а також регіональних, рекогносцирувальних і детальних сейсмічних досліджень,
для пошуку локальних піднять і газових покладів цього комплексу. Zoned prognosis of the Devonian oil- and gas-bearing deposits of Volyn-Podillya
oil- and gas-bearing region is accomplished repeatedly after 25 years of the period of
studying the region. New facts of drilling and geophysical studies have allowed to dismember the section of this complex in detail. The 10 maps of various valuation para-
meters were constructed and modernized that reflected the thickness and lithofacies of
the Upper and Middle Devonian; moreover, were constructed the structure of the bottom
and the thickness of dolomite-anhydrite horizon of Lanivska (Velykomostivska) suite of
the Middle Devonian, the structure of the surface of the Frasnian stage of the Upper Devonian; the thickness of each individual productive horizons of sandstones or the total thickness of sandstones for all the Middle Devonian complex. The most important criteria of
prospects of oil- and gas-bearing of Devonian and the major ways for further exploration
work were determined. The present zoned prognosis includes 12 correlative schemes of
the sections of the 172 boreholes of VPR and adjacent regions, that discovered Devonian
complex entirely or considerable part of it.